Are We Ready for the Future of Work? HR Strategies for AI Literacy and Digital Competency Development - Juhaeni, Unes (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the role of AI literacy and digital competence in enhancing organizational readiness, adaptability, and productivity within the industrial and SME sectors of Banten Province, Indonesia. Responding to the gap in existing literature that often emphasizes infrastructure over human capital adaptability, the research employs a mixed-methods approach, integrating survey data from 312 employees and managers with qualitative insights from in-depth interviews. Statistical analyses reveal that AI literacy significantly strengthens change readiness, particularly in organizations fostering an adhocracy-oriented culture, while targeted, context-specific training programs substantially improve digital competence and stimulate operational innovation. Furthermore, the productivity gains from AI literacy are shown to be contingent upon organizational structures that enable experimentation and adaptive learning. These findings challenge deterministic technology adoption models, demonstrating that leadership commitment and cultural agility can compensate for resource constraints in emerging market contexts. The study contributes theoretically by advancing HRM discourse on cultural mediation in digital transformation and offers practical guidance for workforce-centered strategies that do not rely exclusively on high-capital technological investments. While geographically and temporally bounded, the results provide a foundation for comparative, longitudinal, and causal studies exploring AI readiness in diverse socio-economic settings.